2010
DOI: 10.1590/s1676-06032010000100024
|View full text |Cite
|
Sign up to set email alerts
|

Anurofauna da Floresta Estacional Semidecidual da Estação Ecológica dos Caetetus, Sudeste do Brasil

Abstract: Semi-deciduous Forest is one of the most threatened and deforested vegetation types of Brazil due to its land conversion to agriculture in the beginning of the 20 th Century; its distribution is now reduced to less than 8% of its original extent. Studies about anuran taxocenosis associated to these forests are scarce, even when we consider the remaining areas of pristine forest. We present herein results from an amphibian survey at the Estação Ecológica dos Caetetus, a conservation unit with a singular preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 71 publications
0
21
1
7
Order By: Relevance
“…Even though the species may congregate for breeding throughout the year, with decrease in abundance on nights with temperatures below 15°C (Brassaloti et al, 2010), we recorded calling activities at even lower temperatures in Nova Alvorada do Sul (~8-15°C). All males were calling perched over shrubs and aquatic vegetation, in agreement with Jim (1980), but Melo et al, (2007) also found males calling on the floor.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Even though the species may congregate for breeding throughout the year, with decrease in abundance on nights with temperatures below 15°C (Brassaloti et al, 2010), we recorded calling activities at even lower temperatures in Nova Alvorada do Sul (~8-15°C). All males were calling perched over shrubs and aquatic vegetation, in agreement with Jim (1980), but Melo et al, (2007) also found males calling on the floor.…”
Section: Discussionmentioning
confidence: 73%
“…The record of H. caingua in Nova Alvorada do Sul municipality, Brazil, expands its distribution to approximately 115 km (linear distance) northward (previously northernmost record was between Gália and Alvilândia municipalities, São Paulo -22°24'11" S; 49°42'05" W - Brassaloti et al, 2010) and reaches into the Cerrado phytogeographic domain of Mato Grosso do Sul state, Brazil (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations